2022
DOI: 10.1109/access.2022.3208378
|View full text |Cite
|
Sign up to set email alerts
|

Channel Measurements and Characterizations for Long Range Air-to-Ground Communication Systems in the UHF Band

Abstract: In this paper, we consider long range air-to-ground (AG) communication systems which support aeronautical platforms including unmanned aerial vehicles (UAVs) in the ultra high frequency (UHF) band. For such a system, we present the measurement based path loss analysis and multipath characteristic results at the distance of hundreds of kilometers. To this end, the experimental AG channel measurement system is implemented at the aircraft with various ground station (GS) environments. Through realistic flight tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…is solved for α(b) i -again using the LS approach. Thus, the overall objective of the optimization problem is to minimize the residual (b) i returned by the LS algorithm applied to (14). Using the definition given in (11), this leads to…”
Section: Detection Improvements a Fine Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…is solved for α(b) i -again using the LS approach. Thus, the overall objective of the optimization problem is to minimize the residual (b) i returned by the LS algorithm applied to (14). Using the definition given in (11), this leads to…”
Section: Detection Improvements a Fine Detectionmentioning
confidence: 99%
“…In [14], air-ground channel measurements with a bandwidth of 2 MHz in the Ultra High Frequency (UHF) band have been performed. The authors also provide a model on the path loss and discuss the observed effects of multipath propagation by a statistical evaluation of sets of Channel Impulse Responses (CIRs).…”
Section: Introductionmentioning
confidence: 99%